1998
DOI: 10.1590/s0034-89101998000200002
|View full text |Cite
|
Sign up to set email alerts
|

Mid-upper arm circumference in pregnant women and its relation to birth weight

Abstract: OBJECTIVE: In order to determine the relationship between some maternal anthropometric indicators and birth weight, crown-heel length and newborn's head circumference, 92 pregnant women were followed through at the prenatal service of hospital in S. Paulo, Brazil. MATERIAL AND METHOD: The following variables were established for the mother: weight, height, mid-upper arm circumference, pre-pregnancy weight, gestational weight gain and Quetelet's index. For the newborn the following variables were recorded: birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 6 publications
4
44
1
5
Order By: Relevance
“…In this study it was observed that for a centimeter increase in maternal MUAC, birth weight increased by 13.5 g (β=13.5, P=0.04). Simillar positive association was observed in a study conducted in Brazil where for each centimeter increase in maternal MUAC, there was 45.52 increased in birth weight (Ricalde et al, 1998). Another study conducted in Ethiopia also showed that maternal MUAC of 23+ was positively associated with birth weight (Wado et al, 2014).…”
Section: Discussionmentioning
confidence: 73%
“…In this study it was observed that for a centimeter increase in maternal MUAC, birth weight increased by 13.5 g (β=13.5, P=0.04). Simillar positive association was observed in a study conducted in Brazil where for each centimeter increase in maternal MUAC, there was 45.52 increased in birth weight (Ricalde et al, 1998). Another study conducted in Ethiopia also showed that maternal MUAC of 23+ was positively associated with birth weight (Wado et al, 2014).…”
Section: Discussionmentioning
confidence: 73%
“…Some studies have used maternal MUAC values as indicators of poor pregnancy outcomes; maternal MUAC was also found to be positively correlated with birth weight and other newborn anthropometry (Ricaldo et al, 1998;Elshibly and Schmalisch, 2008;Elshibly and Schmalisch, 2009). Although the mid -upper arm circumference tape has been widely acknowledged as a tool for determining the nutritional status of children several years ago, not many studies have documented MUAC as an indicator of nutritional status in adults.…”
Section: Discussionmentioning
confidence: 99%
“…The mid-point between the acromion process and the olecranon was taken as the site for measurement of the midupper arm circumference. This was recorded in centimeters (cm) (Ricaldo et al, 1998;UNICEF, 2009 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome the limitation of paucity of information on maternal diet, we also measured Maternal Mid Upper Arm Circumference which is reported to be a potential indicator of chronic nutritional status [13]. Recall method for estimating dietary intake and approximation of quantity of food consumed were the other limitations.…”
Section: Discussionmentioning
confidence: 99%